Pathways for resilience in Mediterranean cork oak land use systems - Acácio, Vanda; Holmgren, Milena (Annals of Forest Science, 2012)
& Context Loss of woodlands and degradation of vegetation and soil have been described for all Mediterranean-type ecosystems worldwide. In the Western Iberian Peninsula, overexploitation of evergreen cork oak land use systems has led to soil erosion, failures in oak recruitment, and loss of forests. Degraded and dry sites are quickly colonised by pioneer heathland rockrose (Cistus spp.) shrubs forming highly persistent patches. & Aims Although traditionally shrublands have been considered as a transient successional state, we present evidence that they can represent persistent alternative states to former cork oak forests. & Review trends and conclusions We first describe how Mediterranean vegetation evolved in the Iberian Peninsula and the role of fire and long-term human management as main disturbances. We then discuss alternative pathways through state-and-transition models indicating the ecological and land use variables that halt cork oak regeneration and recruitment and drive vegetation transitions towards persistent shrublands. Unless concerted management actions and restoration programmes are undertaken, the cork oak land use systems will not be sustainable.
Keywords: alternative stable state; cistus; mediterranean-type ecosystem; Quercus suber; resilience; Restoration

Old-field secondary succession in SE Spain: can fire divert it? - Santana, Victor M; Jaime Baeza, M; Marrs, Rob H; Ramón Vallejo, V (Plant Ecology, 2010)
In the Mediterranean Basin, most cultivated areas were abandoned in the last century and are now in various stages of old-ﬁeld succession. The aim of this work was to analyse the successional trajectories of these ecosystems, and to assess possible deviations in these pathways due to ﬁre occurrence at high or low recurrence levels. Old-ﬁelds abandoned either about 50 or about 100 years ago were selected in SE Spain. Within the 50-year-old abandoned ﬁelds, plots were established which had been burned by 1, 2 and 3 ﬁres in the last 25 years. Cover values of vascular species were sampled and then analysed by means of multivariate analysis. Euclidean distances between resulting communities were used as an indicator of the possible deviation from the unburned successional pathway. Our results pointed to the possibility that different successional pathways may exist depending on ﬁre occurrence and recurrence. In the absence of ﬁre, the vegetation is dominated by pioneer species, mainly Pinus. With the passage of time this vegetation will become dominated by later successional tree species (Quercus). However, when early-successional communities are affected by ﬁre, the succession can be diverted. A single ﬁre is enough to change Pinusforests into alternative stable states dominated by Rosmarinus ofﬁcinalis shrub communities, where the colonisation of species in later successional stages is arrested. This deviation increases in high ﬁre recurrence regimes where the vegetation changes to dwarf shrubs and herbs.
Keywords: alternative stable state; Arrested succession; CCA; Fire recurrence; Mediterranean vegetation; Successional pathway